Shedding Light on SARS-CoV-2, COVID-19, COVID-19 Vaccination, and Auditory Symptoms: Causality or Spurious Conjunction? - Saunders, Gabrielle H.; Beukes, Eldre; Uus, Kai; Armitage, Christopher J.; Kelly, Jack; Munro, Kevin J. (Frontiers in Public Health, 2022)
There are reports of associations between SARS-CoV2, COVID-19, COVID-19 vaccines, and auditory symptoms (hearing difficulty, tinnitus). However, most studies have relied on self-report and lack baseline and/or non-COVID control groups. This makes it problematic to differentiate if symptoms are associated with SARS-CoV2, COVID-19, the vaccine, psychosocial factors or recall bias. In this study, we differentiate these by comparing hearing and tinnitus survey data collected pre- and during the pandemic. The survey conducted during the pandemic asked about the onset and change in three types of symptom. Type One—known association (loss of smell, memory/concentration issues, persistent fatigue), Type Two—indeterminate association (auditory symptoms), and Type Three—no established association with COVID-19 (toothache). We hypothesized that if auditory symptoms are directly associated with COVID-19, their onset and change would be similar to Type One symptoms, but if indirectly associated (reflecting psychosocial factors and/or recall bias) would be more similar to Type Three symptoms. Of the 6,881 individuals who responded, 6% reported confirmed COVID-19 (positive test), 11% probably had COVID-19, and 83% reported no COVID-19. Those with confirmed or probable COVID-19 more commonly reported new and/or worsened auditory symptoms than those not reporting COVID-19. However, this does not imply causality because: (1) new auditory symptoms coincided with COVID-19 illness among just 1/3 of those with confirmed or probable COVID-19, and another 1/3 said their symptoms started before the pandemic—despite reporting no symptoms in the pre-pandemic survey. (2) >60% of individuals who had COVID-19 said it had affected their Type 3 symptoms, despite a lack of evidence linking the two. (3) Those with confirmed COVID-19 reported more Type 1 symptoms, but reporting of Type 2 and Type 3 symptoms did not differ between those with confirmed COVID-19 and those without COVID-19, while those who probably had COVID-19 most commonly reported these symptom types. Despite more reports of auditory symptoms in confirmed or probable COVID-19, there is inconsistent reporting, recall bias, and possible nocebo effects. Studies that include appropriate control groups and use audiometric measures in addition to self-report to investigate change in auditory symptoms relative to pre-COVID-19 are urgently needed.